2011
DOI: 10.1111/j.1537-2995.2010.03002.x
|View full text |Cite
|
Sign up to set email alerts
|

Donation frequency of blood donors participating in a prospective cohort study of iron status

Abstract: BACKGROUND Blood centers are interested in understanding determinants of frequent blood donation. We hypothesized that participation in uncompensated research could result in higher donation rates. STUDY DESIGN AND METHODS Donation rates for 2425 subjects from six US blood centers enrolled in the Retrovirus Epidemiology Donor Study-II Donor Iron Status Evaluation Study were compared to those of nonenrolled donors (n = 202,383). Over 15 months, we compared mean donation rates and adjusted rate ratios (RRs) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…Fourth, our findings underscore the potential benefits of effective communication with blood donors about making and keeping donation appointments. Indeed, we found that gains in blood collection achieved through comprehensive reminders were similar to those obtained by reducing inter-donation intervals 36 , 37 (although part of this gain is likely to have been due to the effects of participating in a research study 38 ). Finally, as this trial has identified subsets of donors with readily measured characteristics (eg, those with higher than average ferritin concentrations) who have greater capacity than other donors to give blood more frequently, our study contributes to the possibility of increased personalisation of blood donation.…”
Section: Discussionmentioning
confidence: 55%
“…Fourth, our findings underscore the potential benefits of effective communication with blood donors about making and keeping donation appointments. Indeed, we found that gains in blood collection achieved through comprehensive reminders were similar to those obtained by reducing inter-donation intervals 36 , 37 (although part of this gain is likely to have been due to the effects of participating in a research study 38 ). Finally, as this trial has identified subsets of donors with readily measured characteristics (eg, those with higher than average ferritin concentrations) who have greater capacity than other donors to give blood more frequently, our study contributes to the possibility of increased personalisation of blood donation.…”
Section: Discussionmentioning
confidence: 55%
“…Because the study enrolled a population willing to commit to a 2‐year, longitudinal study on iron status of blood donors, they may have been more likely to take a supplement or to have a previous specific concern for or interest in iron . Comparison of donation rates before and after enrollment in RISE indicate that first‐time donors enrolled in the study had donation rates nearly double that of the general donor population, supporting an interpretation of higher commitment and motivation. Similarly, the higher rate of 35% IS reported in largely unselected donors in the REDS‐III RBC‐Omics study may also reflect unrecognized differences between routine donors and those who enroll in research studies.…”
Section: Discussionmentioning
confidence: 88%
“…Two distinctly different donor groups comprised the RISE study: FT and RA donors (iron stores initially unaffected by blood donation) and frequent donors were asked to return more often than typical repeat donors who in aggregate donate 1.7 times a year 20 . Based on the enrollment criteria for RISE, approximately 54% of all donors giving allogeneic donations at the six REDS‐II blood centers during the enrollment period were eligible for enrollment in RISE (38% of repeat donors and all FT and RA donors—Bahrami and colleagues 22 and unpublished data). These four RISE cohorts represent a population of donors at higher risk of iron depletion considering their high frequency of donation.…”
Section: Discussionmentioning
confidence: 99%